2016
DOI: 10.1681/asn.2016010009
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Trps1 Promotes Tubular Cell Proliferation after Ischemia-Reperfusion Injury through cAMP–Specific 3′,5′-Cyclic Phosphodiesterase 4D and AKT

Abstract: Trichorhinophalangeal 1 (Trps1) is a transcription factor essential for epithelial cell morphogenesis during kidney development, but the role of Trps1 in AKI induced by ischemia-reperfusion (I/R) remains unclear. Our study investigated Trps1 expression during kidney repair after acute I/R in rats and explored the molecular mechanisms by which Trps1 promotes renal tubular epithelial cell proliferation. Trps1 expression positively associated with the extent of renal repair after I/R injury. Compared with wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…To investigate the role of DcR2 in renal fibrosis, green fluorescent protein (GFP)-DcR2 small interfering RNA (siRNA) or overexpression plasmids were injected into the kidney via tail vein under ultrasonography guidance as per the established procedures. 26 As shown in Supplementary Figure S1A and B, GFP was expressed in tubules after control vectorand DcR2-related plasmid transfection, and GFP was coexpressed with DcR2 in mice treated with DcR2-overexpression plasmid. DcR2 mRNA and protein levels were decreased by 74.7% and 69.0% after DcR2-siRNA transfection, respectively, whereas they were increased by 215% and 192% after DcR2-overexpression transfection, respectively (Supplementary Figure S1C-E).…”
Section: Role Of Dcr2 In Renal Fibrosis In Dnmentioning
confidence: 82%
See 1 more Smart Citation
“…To investigate the role of DcR2 in renal fibrosis, green fluorescent protein (GFP)-DcR2 small interfering RNA (siRNA) or overexpression plasmids were injected into the kidney via tail vein under ultrasonography guidance as per the established procedures. 26 As shown in Supplementary Figure S1A and B, GFP was expressed in tubules after control vectorand DcR2-related plasmid transfection, and GFP was coexpressed with DcR2 in mice treated with DcR2-overexpression plasmid. DcR2 mRNA and protein levels were decreased by 74.7% and 69.0% after DcR2-siRNA transfection, respectively, whereas they were increased by 215% and 192% after DcR2-overexpression transfection, respectively (Supplementary Figure S1C-E).…”
Section: Role Of Dcr2 In Renal Fibrosis In Dnmentioning
confidence: 82%
“…Ultrasonography-mediated gene transfer of DcR2-siRNA or DcR2-overexpression plasmid in vivo DcR2-siRNA or DcR2-overexpression plasmid (OBiO Technology, Shanghai, China) was transferred into the kidney of mice using the ultrasonography microbubble-mediated gene transfer technique as per our previously published research. 26 Briefly, the DcR2 expression plasmids were mixed with Sonovue (Bracco, Milan, Italy) at a ratio of 1:1 (vol/vol). For the control vector group, the same amount of empty control plasmids was used.…”
Section: Animal Modelsmentioning
confidence: 99%
“…C1orf54 was reported to potentially function in the pathophysiology of diffuse congenital hyperinsulinism through the IGF-1/mTOR/AKT pathway, 19 and the PI3K/AKT pathway is known to play a critical role in cell proliferation. 20,21 Here, we demonstrated that AKT phosphorylation was inhibited in C1orf54-deficient mice after kidney IRI and that this could be reproduced in HK-2 cells subject to hypoxia/reoxygenation.…”
Section: C1orf54 Overexpression Alleviated Post-iri Renal Dysfunctionmentioning
confidence: 79%
“…Suppressed cell proliferation has been frequently observed during renal iri and the promotion of tubular cell proliferation is the natural response during recovery from renal dysfunction (52,53); for example, the transcription factor transcriptional repressor GaTa-binding 1, which was initially characterized as an essential regulator of cell morphogenesis during kidney development, promoted tubular cell proliferation following iri through regulating cyclic AMP-specific 3' ,5'-cyclic phosphodiesterase activity and aKT signaling, and it is thus viewed as a potential target for treating kidney iri (53). in the present study, it was demonstrated that PHC treatment significantly promoted renal cell proliferation, alongside increasing Bcl-2 expression levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%